Prototype Model Development and Design Analysis of A Solar Tricycle for Physically Challenged People in India - Dr. Ashis Acharjee; Suprakash Debnath; Mainak Nath; Gracy Hrangkhawl; Dhananjay Kanaujiya; Madhujit Deb (International Journal of Mechanical Dynamics and Systems Analysis, 2023)
Society is greatly concerned about the mobility of individuals with physical disabilities. The scarcity of energy resources and the issue of pollution are currently the primary concerns. These issues can be resolved by employing alternative energy sources such as solar power. This paper presents an overview of the existing solar tricycles designed for those with disabilities. It also improves a handicapped-friendly solar-powered tricycle. The goal is to reduce handicapped people's physical exertion, making it suitable for India. This research explores the utilization of solar power using solar panels or photovoltaic cells to operate a brushless DC motor, battery, controller, throttle, and other components with minimal human effort. The design specifications were determined by analyzing the issues faced by disabled individuals, conducting a general survey on disabled people who use tricycles, and considering the input of experts working with disabled individuals. These factors helped determine the solar tricycle's design needs. New solar tricycles are smarter and more efficient. This solar three-wheeler, designed for physically disabled people in our country, has many features to improve maneuverability, solar energy utilization, biomechanics and comfort, suspension, all-terrain traffic, and ease of use. The countershaft, sprocket, chain, bearing, and other components are being designed in this study. Solar tricycles require careful selection of a solar panel, DC motor, battery, and power requirements for drives and battery charging. The solar panel's rated power must also be established. All these elements were considered to create a new, improved, and efficient solar tricycle. Its steel structure supports a solar panel, battery, charging pack, drive system, and braking system. Electricity powers this solar system, so it doesn't emit harmful compounds. This tricycle uses a mechanical drive mechanism to remove manual effort for disabled people. It is cheaper than a traditional engine vehicle. The paper details Solar Tricycle construction and operation. We created the Solar Tricycle blueprint using data from various journals. This study tested numerous Solar Tricycle components' functions. The computations and expected results are discussed. The findings suggest it can exceed 15 km/h. After a full charge, the device can run for 4 hours. Additionally, it can hold 120 kilograms. Thus, the solar-powered tricycle allows disabled people to use it anywhere, even without electricity.
Keywords: Development of solar tricycle, Economical; Handicapped person; Solar Tricycle; design of solar tricycle